Palivizumab and prevention of childhood respiratory syncytial viral infection: protocol for a systematic review and meta-analysis of breakthrough infections - Meghan Sebastianski; Robin Featherstone; Shelly Jun; Joan Robinson (BMJ Open)
Introduction Childhood respiratory syncytial virus (RSV) infection is a global phenomenon that can lead to fatal respiratory illness. Palivizumab is a drug that is routinely used in affluent countries as a prophylaxis against RSV infection; nevertheless, breakthrough infections are often reported. In light of new findings on potential RSV resistance to palivizumab, an up-to-date synthesis of evidence on effectiveness is needed. Furthering existing reviews, a broadened scope to better reflect effectiveness in a ‘real world’ clinical context is also important. This systematic review and meta-analysis will enhance our understanding of the effectiveness of palivizumab in varying populations of children. Findings from this review will inform recommendations for best practices regarding palivizumab use for childhood RSV infection as well as research priorities in RSV vaccine development.Methods and analysis We will conduct a systematic review of primary population-based studies that examine the incidence of palivizumab breakthrough infections in children, published between 1997 to present. In collaboration with a research librarian, four electronic databases (MEDLINE, Embase, Cochrane Library, Web of Science) and additional sources will be searched. Study screening and quality assessment will be performed in duplicate. Data will be extracted by one reviewer, with partial and random verification by a second reviewer. The primary outcomes to assess breakthrough RSV infection will be hospitalisation, length of stay and the need for intensive care unit admission and mechanical ventilation in children receiving palivizumab. The secondary outcome will be RSV-associated mortality. We will conduct a meta-analysis using pooled effectiveness data, and include subgroup analyses by patient comorbidities and drug compliance. Sensitivity analyses for risk of bias and study design will also be performed.Ethics and dissemination This systematic review will only include data from previously published literature and is therefore exempt from ethics approval. Final results will be disseminated through peer-reviewed publication and presented at academic conferences and scientific meetings engaging paediatric researchers and healthcare providers. Should findings from this review necessitate updates to current clinical practice guidelines, we intend to establish a working group to engage relevant health administrators and decision makers.PROSPERO registration number CRD42019122120.